The Effect of Video Education on Anxiety and Quality of Life in Breast Cancer Patients: A Systematic Review - Desika Anita Gultom; Jenny Marlindawani; Hasnida Hasnida (Universitas Pahlawan Tuanku Tambusai, 2026)
Introduction: Breast cancer most often attacks women so more women will seek medical attention when breast cancer is suspected if public health education is provided to raise awareness among women about the disease's symptoms, as well as the significance of early identification and treatment. Managing psychosocial needs involves a variety of services and activities, from educational initiatives to direct nursing measures. Patients can learn more about their illness, the course of therapy, and coping mechanisms for a range of mental and physical difficulties by watching films. Methods: The source of the 9 articles using relevant keywords based on the title of the research obtained from a database among them PubMed, Googleschoolar and ProQuest. Articles were selected using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) diagram method. Results: The 9 articles in this systematic review interventions from the articles in this systematic review were divided mobile app-based educational interventions (via a chat application) and website-based interventions to provide support to women from the start of their first chemotherapy cycle until the commencement of the third cycle, spanning a total of 7 weeks. The application was enriched with visuals, audio and video CDs so that the users could comprehend the information more easily and the content be interesting. Conclusion: Findings from this systematic review suggest that mobile app-based educational interventions (via a chat application) and website-based intervention in breast cancer can help reduce the anxiety and increase quality of life.